Waste and Accurate Management of Raw Material Inventory in Wood Companies - Ermawati, Emmy (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2020)
Data obtained from the statistical office shows that Lumajang Regency, in general, is one of the largest albasia wood producers in East Java Province. Albasia wood is basically easily cultivated and minimal maintenance and is able to grow well even though the land is categorized as infertile. This is what makes people more interested in growing Albasia wood. The research objective is to analyze the optimal albasia wood raw material volume needed, to analyze the total cost of supplies, to analyze when a reorder point for albasia wood raw material is carried out, to analyze the amount of albasia wood safety stock that must be provided. Direct observation and observation activities in the field as well as taking documentation, interviews and discussions with CV. JAZINDO employees. Data Analysis Data analysis was done in a descriptive qualitative manner by recording to describe the state of the object under study based on facts and conditions that occurred in the field. Based on the results of data collection, calculation and analysis of data in 200 cm albasia wood are 945 m3, and for 260 cm albasia wood is 72 m3. Purchase of raw materials needs to be done after the inventory reaches the ROP limit. Safety stock calculation, obtained safety supplies for each type of albasia wood, namely 1543 m3 for albasia 100 cm wood, 548 m3 for albasia 130 cm wood, 848 m3 for albasia wood 200 cm, and 56 m3 for albasia wood 260 cm. With the EOQ method, it is recommended to order wood at calculated intervals.